The Effect of Dysmenorrhea Exercises on Menstrual Pain Intensity in Adolescent Girls at SMPN 1 Tumpang - Febriana Dian Reza; Nila Widya Keswara; Retno Dewi Prisusanti (Journal of Community Health Provision, 2026)
The prevalence of menstrual pain, or dysmenorrhea, among adolescent girls remains quite high, and this condition often presents a significant obstacle to their learning. This study was conducted with the specific objective of examining the effectiveness of dysmenorrhea exercise interventions in reducing menstrual pain levels among female students at SMPN 1 Tumpang. Using a quasi-experimental method with a non-equivalent control group design, this study sought to examine the effect of physical activity on student comfort. The population involved included all seventh-grade female students experiencing menstrual pain, with a sample of 30 respondents determined using a simple random sampling technique. All respondents were grouped into two categories: the intervention group and the control group. Pain levels were measured using the Numeric Rating Scale (NRS) before (pre-test) and after (post-test) the intervention to ensure data accuracy. Statistical data processing was performed using the Wilcoxon Signed Rank test to assess changes within groups and the Mann-Whitney test to compare differences between groups. The test results demonstrated a significant reduction in pain intensity in respondents who received the exercise intervention, with the average pain level dropping from moderate to mild. This contrasted with the control group, which tended to remain stable and showed no significant change in pain levels. Based on these statistical tests, it can be concluded that the application of dysmenorrhea exercises has a significant effect on reducing menstrual pain. These findings also confirm that dysmenorrhea exercises can be a safe, practical, and efficient alternative non-drug self-help solution for adolescent girls to address discomfort during the menstrual cycle.